2020
DOI: 10.1093/alcalc/agaa012
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption by Beverage Type and Risk of Breast Cancer: A Dose-Response Meta-Analysis of Prospective Cohort Studies

Abstract: Aims Alcohol intake has been shown to increase the risk of breast cancer. However, the dose-response analysis of different alcoholic beverages (spirits, wine and beer) is not clear. Our meta-analysis aims to provide a dose-response estimation between different alcohols and breast cancer risk. Methods Search of PubMed and Web of Science and manual searches were conducted up to 1 December 2018, and summary relative risks (RRs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 37 publications
2
41
1
Order By: Relevance
“…Although these limitations, our study provides a comprehensive description of FBC-related deaths attributable to the five well-known risk factors at the secular, spatial, and population levels. Our findings are important complements to the previous studies [ 18 , 44 ].…”
Section: Discussionsupporting
confidence: 88%
“…Although these limitations, our study provides a comprehensive description of FBC-related deaths attributable to the five well-known risk factors at the secular, spatial, and population levels. Our findings are important complements to the previous studies [ 18 , 44 ].…”
Section: Discussionsupporting
confidence: 88%
“…In addition, certain alcoholic drinks could be a more serious problem. A meta-analysis showed that breast cancer risk significantly increased with a high intake of wine, rather than beer and spirits [18]. Soju and beer have the highest levels of consumption among alcoholic beverages in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Despite clear epidemiological evidence that alcohol consumption is a risk factor for breast cancer [1], women's awareness of the alcohol-breast cancer link remains considerably low [2]. While portrayals of the alcohol-breast cancer link within the media could be an avenue to increase women's awareness, there has been conflicting messages as to whether alcohol is a harmful or helpful substance to health generally.…”
Section: Introductionmentioning
confidence: 99%